2021
DOI: 10.1515/med-2021-0381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of remifentanil and propofol on distant organ lung injury in an ischemia–reperfusion model

Abstract: Our aim was to evaluate lung injury due to oxidative stress and antioxidant activity levels in an infrarenal ischemia–reperfusion model and to compare prevention effects of single and combined use of propofol and remifentanil. In this study, a total of 40 adult Wistar Albino rats were randomly divided into five groups of eight rats as SHAM, physiological saline, intraperitoneal propofol, remifentanil, and propofol and remifentanil groups. Blood and tissue samples were obtained after 80 min of reperfusion. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…[18], they showed that in patients undergoing anaesthesia induction with propofol and thiopental, propofol inhibited the cellular oxidative damage measured in platelets and glutathione increased antioxidant defence. In the study of Kanbak et al (19), histological examination showed that propofol reduced the negative effects of I/R on tissues, while remifentanil was not as effective as propofol.…”
Section: Discussion Conclusionmentioning
confidence: 96%
“…[18], they showed that in patients undergoing anaesthesia induction with propofol and thiopental, propofol inhibited the cellular oxidative damage measured in platelets and glutathione increased antioxidant defence. In the study of Kanbak et al (19), histological examination showed that propofol reduced the negative effects of I/R on tissues, while remifentanil was not as effective as propofol.…”
Section: Discussion Conclusionmentioning
confidence: 96%